一次函数,要有过程

职业培训 培训职业 2025-01-02
解:(1)将x=1代入,f(1)=2+a=4,所以a=2,(2)设f(x)=ax+b,则f(2)=2a+b=8,f(-6)=-6a+b=4,联立上述二式,a=1/2,b=7,所以f(x)=x/2+7,f(12)=12/2+7=13,(3)直接代入,f(1)=k+b=2f(3)=3k+b=3解之得:k=1/2,b=3/2,(4)直接代入,f(1)=a+b=-2f(-1)=-a+b=0解之得:a=-

解:

(1)将x=1代入,

f(1)=2+a=4,

所以a=2,

(2)设f(x)=ax+b,

则f(2)=2a+b=8,

f(-6)=-6a+b=4,

联立上述二式,a=1/2,b=7,

所以f(x)=x/2+7,

f(12)=12/2+7=13,

(3)直接代入,

f(1)=k+b=2

f(3)=3k+b=3

解之得:k=1/2,b=3/2,

(4)直接代入,

f(1)=a+b=-2

f(-1)=-a+b=0

解之得:a=-1,b=-1

(5)当2x+1=a时

x=(a-1)/2

所以f(a)=3(a-1)/2-2=4

可解得,a=5.

标签

版权声明:本文由哟品培原创或收集发布,如需转载请注明出处。

本文链接:http://www.yopinpei.com/20250102/2/1112679

猜你喜欢
其他标签